Teori Keagenan dan Teori Akuntansi Positif sebagai Dasar Teoretis dalam Praktik Earnings Management - Ericha Abmiekawati (Masyarakat Ekonomi Syariah Bogor, 2026)
Earnings management has become a significant element in contemporary accounting practices due to its direct relationship with the quality of financial reporting and economic decision-making processes. This practice is generally viewed as a managerial response to various economic incentives and contractual pressures inherent in corporate organizations. This article aims to examine the phenomenon of earnings management using Agency Theory and Positive Accounting Theory as the primary conceptual frameworks. The research method employed is a qualitative approach through a literature review of classical textbooks as well as relevant national and international journal articles, including recent empirical studies published within the period 2000–2025. The results of the review indicate that Agency Theory explains the emergence of earnings management practices as a consequence of conflicts of interest and information asymmetry between principals (those who delegate authority) and agents (those who receive the mandate). Meanwhile, Positive Accounting Theory explains managers’ tendencies and accounting policy choices through the bonus plan hypothesis, debt covenant hypothesis, and political cost hypothesis. In addition, recent literature findings indicate a shift in earnings management patterns from accrual-based methods toward manipulation through real business activities. This article concludes that earnings management is a rational behavior of agents that can be predicted within an economic incentive framework, although such practices have the potential to reduce the quality of accounting information. This, in turn, may diminish the relevance, reliability, and faithful representation of financial statements, thereby increasing information risk for investors. This study contributes by presenting an integrated synthesis of Agency Theory and Positive Accounting Theory in explaining earnings management practices, particularly in the context of firms operating in developing countries, such as Indonesia.